Misconception as a critical and creative thinking inhibitor for mathematics education students - Rochmad, Rochmad; Kharis, Muhammad; Agoestanto, Arief; Zahid, Muhammad Zuhair; Mashuri, Mashuri (Unnes Journal of Mathematics Education, 2018)
The accurate understanding of critical thinking and mathematical creativity in solving the current problem is still difficult to standardize. These two thinking skills are indispensable to anyone who is studying mathematics, especially for Undergraduate Mathematics students who are studying Linear Algebra. However, the difficulties in critical thinking discourage students to think creatively and mathematically. In linear algebraic subject matter, many problems require critical reasoning. It goes without saying that the difficulties in various reasoning aspects critically cause other difficulties in developing creative thinking aspects. Further, mathematical critical thinking skills in solving problems require a background in understanding the concepts related to the problem faced. In addition, the failure to understand and connect between concepts in solving linear algebra problems makes it worst and difficult to critically and creatively think.